DESAIN KONVERTER CUK PADA METODE PENGEREMAN REGENERATIF EKSITASI MANDIRI PADA MOTOR INDUKSI 3 FASA - Ayatullah Farhan; Waru Djuriatno; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
The existence of transportation in Indonesia plays a very important role in facilitating human mobility to move from one place to another. The use of electric vehicles is one of the developments that is currently experiencing a lot of progress, including electric trains (KRL). As the name implies, KRL is sourced from electricity which is supplied to the train system, which is mainly used as a motor drive. When using a motorbike, the important parameter to consider is braking. One type of electric braking that is widelydeveloped is regenerative braking. Self-excitation method regenerative braking using a capacitor is one of the branches of regenerative braking. This type of braking uses motor excitation which will be stored in a capacitor. The resulting regeneration energy will be stored in a battery so that it is not wasted as heat alone, therefore to transfer power a DC-DC converter is needed to adjust the battery voltage. The CUK converter is selected to buck/boost the voltage to match the battery specifications. This research was carried out by simulating using Simulink/MATLAB software which is useful for analyzing the input and output of theconverter and the state of charge (SoC) on the battery. Based on the simulation, it shows that the output of the converter produces a voltage of 13.40 V at a grid frequency of 50 Hz with a SoC increase of 0.006426%. The test was carried out over the grid frequency range of 10-100 Hz which resulted in varying voltage errors and SoC increases.Kata Kunci— Things Three Phase Induction Motor, Regenerative Braking, DC-DC Converter, Capacitor, Frequency, State of Charge (SoC)